Brubaker [videorecording (DVD)] - Keith, David, 1954-; Hamilton, Murray; McIntire, Tim; Redford, Robert; Kotto, Yaphet, 1939-2021-; Alexander, Jane, 1939- (Twentieth Century Fox Home Entertainment, 2003)
Based on the true story of a reform warden who risks his life to replace brutality and corruption with humanity and integrity in a state prison farm.